Problem with draggers : Port Aux Choix - Memorial University of Newfoundland. Extension Service (Producer) (MUN Extension Service, 1968)
Interview with two fishermen who lost over 20 nets to draggers. They discuss the economic implications of this on their families and the hardships of fishing under such threatening conditions. They also discuss the government decision to cover their losses and provide them with new equipment.